Analisis Pengaruh Price Discount, Online Customer Review Dan Online Customer Rating Terhadap Keputusan Pembelian Pada Produk Brand Jims Honey - Cheesa Imaniar; Siti Asiyah; Kartika Rose Rachmadi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine and explain Price Discounts, Online Customer Reviews and Online Customer Ratings on Purchasing Decisions (Case Study of Jims Honey Consumers). This research includes a type of research with quantitative. The method used is multiple linear regression. The sampling technique uses the formula from Maholtra with the calculation results of 65 samples. To solve the problems in this study using SPSS with the help of validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that simultaneously. Variable Price Discount (X1), Online Customer Review (X2), and Customer Rating (X3), have a significant effect simultaneously on Purchase Decision (Y). And there is a partial effect between Price Discount (X1) on purchasing decisions, Online Customer Review (X2) has an effect on purchasing decisions, and Online Customer Rating (X3) has an effect on purchasing decision. Keywords: Price Discount, Online Customer Review, Customer Rating, Purchase Decision